My friends call me monster - "Stine, R.L" (Scholastic Inc: New York, 2009)
Michael Munroe learns to never trust a teacher that calls his students "Little Monsters" when he finds himself trapped in Horrorland after a lunch with the suspicious teacher
Keywords: Horror fiction